Community-based prioritization and conservation planning of wild edible plants: Insights from Turkana County, Kenya - Oduor, Francis; Mulwa Kaindi, Dasel; Abong, George; Thuita, Faith; Kettle, Christopher; Termote, Celine (2024)
Wild Edible Plants (WEPs) play a crucial diets in Turkana: • provide 12-30% of dietary intake • average of 76% of micronutrients to consumers' diets.